EARLY DETECTION OF GEAR TOOTH CRACKING FAULT BASED ON RESONANCE BAND AMPLITUDE-PHASE DEMODULATION TECHNIQUE - SUN ShouBao; GUO Yu; WU Xing (Jixie qiangdu)
Several traditional gear diagnosis methods are reviewed. The narrow band demodulation method is often accompanied with low-frequency interference and the resonance demodulation technique is limited in amplitude demodulation.According to the pros and cons of the traditional methods,the resonance band amplitude-phase demodulation technique was proposed for local gear fault detection to compensate the current gear diagnosis methods. It’s a method that taking the resonance frequency as carrier frequency instead of meshing harmonics,hence the low-frequency interference can be suppressed. Amplitude demodulation incorporated with phase demodulation will make the diagnosis more accurate. In this scheme,the fast kurtogram is firstly used to find out the resonance band. Then take the resonance frequency as carrier frequency and implement the resonance band amplitude-phase demodulation program gets both the amplitude and phase modulation functions,which would indicate the gear fault. Simulation and experiment studies indicated that the proposed method is an effective tool for early gear tooth cracking fault detection.